AI-GENERATED CONTEXTUAL LISTENING MATERIALS EXPLORING TEACHER AND STUDENTS PERCEPTIONS IN EFL CLASSROOMS - Mikael Albinus Silitonga; Dedi Irwan; Rahayu Meliasari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
English listening materials in schools frequently lack relevance to students' lives due to resource limitations. This study aims to explore students' and teacher’s perceptions of AI-generated contextual listening materials. Employing a descriptive qualitative design, data were collected through interviews and observations from three ninth-grade students and one English teacher at State Junior High School 1 Sintang, and subsequently analyzed thematically. The findings revealed positive responses from students, as they felt more confident and comprehended the lessons more easily through familiar local content (such as the narrative of Bukit Kelam), effectively reducing their cognitive load. Students also highlighted technical challenges regarding the inconsistent clarity of the AI-generated audio. From the teacher's perspective, AI proved to facilitate the customization of localized materials that are typically difficult to find in conventional resources. However, the teacher emphasized that AI outputs require human editing and collaborative feedback to align with formal pedagogical standards. In conclusion, integrating AI into the Contextual Teaching and Learning (CTL) approach is highly effective for developing culturally relevant materials and enhancing students' learning motivation, provided it is balanced with appropriate instructional design by the teacher